Model parameters versus gas pressure in two different plasma focus devices operated in Argon and Neon - Al Hawat, Sh.; Akel, M.; Lee, S.; Saw, S. H. (Springer US, 2012)
For the plasma focus device AECS PF-2 operated in Ar and INTI PF in Ne, model parameters of mass and current in the axial phase of plasma focus were found by matching the measured and calculated current waveforms over a range of pressures. The results show a value of fm = 0.05 ± 0.01 over 0.2–1.2 Torr in Ar; and fm = 0.04 ± 0.01 over 0.7–4.1 Torr in Neon. The value of fc = 0.7 was fitted for all cases. Combining these results with those published for several other small machines it would appear that, where measured current waveforms are not available for example in designing new machines, a good compromise would be to take a guideline value of fm = 0.05 and fc = 0.7 for both Argon and Neon.